BIMBINGAN BELAJAR VOCABULARY UNTUK MENINGKATKAN MINAT BELAJAR BAHASA INGGRIS KELAS 5 DAN 6 SDN KABINUANG DAMPAL UTARA - Fauzan Azima; Moh. Firmansyah (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase the interest of 5th and 6th grade students at SDN Kabinuang, Dampal Utara, in learning English through tutoring that focuses on vocabulary mastery. The background of the problem shows a low interest in learning English among students, which is largely due to a lack of understanding of basic vocabulary and a lack of variety in learning methods. Therefore, this tutoring approach was designed to overcome these challenges in a more interactive and enjoyable way. The methods used in this activity included direct delivery of material, educational games, and quizzes specifically designed to enrich students' vocabulary. The results of this activity show a significant increase in student enthusiasm and participation in each learning session. Students not only demonstrate a better understanding of new vocabulary, but are also more motivated to actively communicate in English. The conclusion of this community service is that tutoring that focuses on vocabulary is an effective strategy for fostering interest in learning English among elementary school students. Recommendations for the future include the need for similar programs to be continued with longer durations and more diverse materials for significant result.